Method for reconstructing individualized external exposure dose of persons living in a contaminated area with radionuclides as a result of the Chernobyl accident - Куликович, Дмитрий Борисович; Vlasova, Natalie; Visenberg, Yuliya; Kuznetsov, Boris (Journal of the Belarusian State University. Ecology, 2024)
Dose (individual / individualized) assessment is necessary to solve problems of establishing the «dose-effect» relationship and assessing radiation risk, recognizing the most exposed groups of the population in order to provide them medical care. Reliable information on external exposure doses to the population can be obtained on the basis of individual dosimetric control data, however, the use of this method in areas subject to radioactive contamination is a rather labor-intensive problem. If this data is insufficient or no, a correct assessment of the accumulated dose can be made on the basis of forecast estimates according to guidelines; however, existing guidelines for assessing individualized external exposure doses are over-conservative: at best, they allow the calculation of average group (average age) exposure doses. These methods don’t in any way correspond to the task of dose individualization. This determines the relevance of developing an adequate methodological approach to assessing individualized external exposure doses accumulated since the Chernobyl accident. The research sample was formed on the basis of the individual dosimetric control data of residents of the Gomel region for the period from 1988 to 1995. As a result of the research, provisions were statistically substantiated that contribute to expanding the understanding of the patterns of formation of external exposure doses for the population living in contaminated areas with radionuclides. The dependence of individual external exposure doses on the demographic and social characteristics of the individual has been established. A method of reconstruction of individualized external exposure doses has been developed, the basis of which is a statistical model of multiple linear regression. The target factor of the model is the individual annual external exposure dose; explanatory factors are: the contamination density with 137Cs of the territory of a populated area, occupational employment and demographic characteristics of the individual. The model was verified using a generated control sample. The estimation error was 10%. But additionally takes into account the indirect factor - the individual’s occupational employment. The developed method makes it possible to calculate with high accuracy individualized annual external exposure doses in the lack of individual dosimetry control data. The individualized accumulated external exposure doses of calculated in this way, along with the individualized accumulated internal exposure doses, will be used in radiation epidemiological researches to establish the «dose-effect» relationship and assess radiation risks.